The ‘extremely ancient' chromosome that isn't: a forensic bioinformatic investigation of Albert Perry's X-degenerate portion of the Y chromosome - Elhaik, Eran (Nature Publishing Group, 2014)
Mendez and colleagues reported the identification of a Y chromosome haplotype (the A00 lineage) that lies at the basal position of the Y chromosome phylogenetic tree. Incorporating this haplotype, the authors estimated the time to the most recent common ancestor (TMRCA) for the Y tree to be 338 000 years ago (95% CI=237 000–581 000). Such an extraordinarily early estimate contradicts all previous estimates in the literature and is over a 100 000 years older than the earliest fossils of anatomically modern humans. This estimate raises two astonishing possibilities, either the novel Y chromosome was inherited after ancestral humans interbred with another species, or anatomically modern Homo sapiens emerged earlier than previously estimated and quickly became subdivided into genetically differentiated subpopulations. We demonstrate that the TMRCA estimate was reached through inadequate statistical and analytical methods, each of which contributed to its inflation. We show that the authors ignored previously inferred Y-specific rates of substitution, incorrectly derived the Y-specific substitution rate from autosomal mutation rates, and compared unequal lengths of the novel Y chromosome with the previously recognized basal lineage. Our analysis indicates that the A00 lineage was derived from all the other lineages 208 300 (95% CI=163 900–260 200) years ago.